Pengaruh Prinsip-prinsip Good Corporate Governance dan Budaya Organisasi terhadap Kinerja Karyawan - Reska Sukma Parenza; Rini Lestari (UNISBA Press, 2022)
Absract. In a company, optimizing employee performance is an important point in realizing company goals. Some aspects that need to be considered include the principles of good corporate governance and organizational culture. This can affect the increase in employee performance so that the company's goals are achieved optimally. This study aims to determine the effect of the principles of good corporate governance and organizational culture on employee performance. This study uses primary data sources obtained through questionnaires. The sampling technique used in this study is non-probability with convenience sampling technique. The sample of this research is 10 KC and KCP Bank Syariah Indonesia in the city of Bandung and respondents in this study amounted to 54 respondents. The results showed that the principles of good corporate governance of Bank Syariah Indonesia in the city of Bandung had the criteria